Selective credit policies: a survey - SILBER, W.L. (PSL Quarterly Review, 2013)
This survey reviews both the theoretical and empirical literature on selective credit policies. The major concern with most of the researchers in this area has been the range of conditions under which selective policies are effective. The author fist looks at selective credit policies and their real versus financial effects. The effectiveness of selective credit policies in theory and in practice is then analysed in order to determine where in the spectrum of conditions the real world fits. Finally, the costs, efficiency and equity of credit controls are considered in the concluding section. JEL: E51, E52